An algebra problem by Madhavan V

Algebra Level 2

Let x 1 , x 2 x_1,x_2 be the roots of the quadratic equation x 2 + a x + b = 0 , x^2+ax+b=0, where a a and b b are complex numbers, and y 1 , y 2 y_1,y_2 are the roots of the equation y 2 + a y + b = 0 y^2+| a |y+| b|=0 .

If x 1 = x 2 = 1 , | x_1 |=| x_2 |=1, what is y 1 + y 2 = ? | y_1|+| y_2 |= ?


Note: | \cdot | denotes the absolute value function.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Pongkiaet Topar
Sep 5, 2017

x 1 x_{1} and x 2 x_{2} be roots of x 2 + a x + b = 0 x^{2} +ax + b = 0 and x 1 = x 2 = 1 \left |x_{1} \right | = \left |x_{2} \right | = 1

let x 1 = x 2 = p + q i x_{1} = x_{2} = p + qi ------ (no matter what p p equal to q q or not )

which a = 2 p + 2 q i -a = 2p + 2qi and b = ( p 2 q 2 ) + 2 p q i b = \left ( p^{2}-q^{2} \right ) + 2pqi

a = a = 2 p 2 + q 2 \left |-a \right | =\left |a \right |= 2\sqrt{p^{2} + q^{2}} and b = ( p 2 q 2 ) 2 + 4 p 2 q 2 \left |b \right | = \sqrt{\left ( p^{2} - q^{2} \right )^{2} + 4p^{2}q^{2}}

a = 2 \left | a \right | = 2 and b = p 4 + q 4 + 2 p 2 q 2 = ( p 2 + q 2 ) 2 = 1 \left |b \right | = \sqrt{p^{4} + q^{4} + 2p^{2}q^{2}} = \sqrt{\left ( p^{2} + q^{2} \right )^{2} } = 1

leads to

y 2 + a y + b = y 2 + 2 y + 1 = ( y + 1 ) 2 = 0 y^{2} + \left | a \right | y + \left | b \right | = y^{2} + 2 y + 1 = \left (y+1 \right )^{2} =0

then y 1 + y 2 = 1 + 1 = 2 \left |y_{1} \right | + \left | y_{2} \right | = \left | -1 \right | + \left | -1 \right | = 2

Sahil Sharma
Oct 14, 2017

Consider a and b as real as all real numbers are complex and apply Vieta's formula

Paras Lehana
May 22, 2017

Given x 1 x_1 , x 2 x_2 be roots of x 2 + a x + b = 0 x^{2} + ax + b = 0

x 1 x 2 = b x_1x_2 = b (Product of roots) = > x 1 . x 2 = b => | x_1 |.| x_2 | = | b | = > b = x 1 x 2 = 1.1 = 1... ( 1 ) => | b | = | x_1x_2 | = | 1.1 | = 1 ... (1)

Also, x 1 + x 2 = a x_1 + x_2 = -a (Sum of roots) = > x 1 + x 2 = a = a => | x_1 + x_2 | = | -a | = | a | = > a 2 = x 1 + x 2 2 = x 1 2 + x 2 2 + x 1 x 2 ˉ + x 1 ˉ x 2 = 1 + 1 + x 1 x 2 + x 2 x 1 . . . f r o m ( 1 ) => | a |^{2} = | x_1 + x_2 |^{2} = | x_1 |^{2} + | x_2 |^{2} + x_1\bar{x_2} + \bar{x_1}x_2 = 1 + 1 + \frac{x_1}{x_2} + \frac{x_2}{x_1} ... from (1) = > a 2 = 2 + x 1 2 + x 2 2 x 1 x 2 = 2 + ( x 1 + x 2 ) 2 2 x 1 x 2 x 1 x 2 = 2 + a 2 2 b b => | a |^{2} = 2 + \frac{ x_1^{2} + x_2^{2} }{ x_1x_2 } = 2 + \frac{ (x_1 + x_2)^{2} - 2x_1x_2 }{ x_1x_2 } = 2 + \frac{a^{2} - 2b}{b} = \frac{a^{2}}{b}

Now, given y 1 y_1 , y 2 y_2 be roots of y 2 + a y + b = 0 y^{2} + |a|y + |b| = 0

y 1 y 2 = b = 1... f r o m ( 1 ) y_1y_2 = |b| = 1 ... from (1)

y 1 + y 2 = a = a | y_1 + y_2 | = | - |a| | = | a | = > y 1 2 + y 2 2 = a 2 y 1 y 2 ˉ y 1 ˉ y 2 = a 2 b y 1 y 1 ˉ y 2 y 2 ˉ = 2 => | y_1 |^{2} + | y_2 |^{2} = | a |^{2} - y_1\bar{y_2} - \bar{y_1}y_2 = \frac{a^{2}}{b} - \frac{y_1}{\bar{y_1}} - \frac{y_2}{\bar{y_2}} = 2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...